Effectiveness of biological geotextiles for soil and water conservation in different agro-environments - R. Bhattacharyya (2018)
Available studies do not allow comparison and quantification of the effects of biological geotextiles on runoff and water erosion rates under different agro-environmental conditions. Hence, this paper addresses this issue by comparing runoff and soil loss data obtained from field experiments (using different types of biological geotextiles) conducted in the United Kingdom, Hungary, South Africa, China, Thailand and Vietnam. Palm leaf mats (Borassus and Buriti mats) were used in the European countries. In the UK, Borassus mats were used as whole plot cover (area coverage ∼76 per cent; termed Borassus completely covered to differentiate from the Borassus buffer strip plots) and as buffer zones (area coverage ∼10 per cent), whereas Buriti mats were used only as buffer zones (area coverage ∼10 per cent). Only Lala mats were used in South Africa. Elsewhere (China, Thailand and Vietnam) biological geotextiles were constructed using other indigenous local materials, such as bamboo, rice straw and maize stalks. Biological geotextiles were used on bare plots in South Africa and the European countries. In the UK, plots were maintained bare by need based herbicide spraying. However, in South Asia, different crops were grown on the geotextile-covered plots. Results suggest that biological geotextiles were very effective for soil erosion control in all locations and the effectiveness for decreasing soil erosion rates by water was in the range of ∼67-99 per cent. The effectiveness of biological geotextiles in reducing runoff volume was in the range of ∼26-81 per cent. In the UK, total runoff and soil loss (during 8 January 2007-6 May 2008; total precipitation=1145.8mm) from the Borassus (one metre wide) buffer zone plots (cover percentage ∼7.6 per cent) were, respectively, ∼81 and ∼93 per cent less than bare plots. In Hungary and China, plots with ∼38 and 22 per cent geotextile-cover, respectively, had ∼88 and 96 per cent less soil loss, than bare plots. In most months with low precipitation (depth) in Hungary and the UK, runoff volume was greater from plots with geotextile-cover than from bare soils. However, complete data sets indicate that in the UK and Hungary, runoff reduction by different treatments over bare plots ranged between ∼26 and 81 per cent. Results from the UK showed that plots with buffer strips of Borassus and Buriti mats had similar effects in reducing soil losses as completely covered plots of the Borassus mats. Thus, foreseeing biological geotextile-cover on vulnerable segments of the landscape is highly effective for soil erosion control. © 2011 John Wiley & Sons, Ltd.